The Sinosphere and beyond: essays in honor of Joshua Fogel - Judge, Joan; Kurtz, Joachim; Sela, Ori; Shao, Dan; Shapiro, Hugh (De Gruyter, 2024)
The history of East Asia can be most productively studied through a transnational, translingual, and transcultural approach to the region. In The Sinosphere and Beyond, twenty-six leading and emerging scholars use such approaches in rich clusters of essays on Historiography, Sino-Japanese Encounters, Law and Justice, Politics, Art, Literature, and Translation. Each essay builds on the legacy of Joshua Fogel, whose scholarship defined the contours of the Sinosphere in the Western world and beyond. The collection will be of interest to scholars and students with specific research concerns within these broader rubrics: from the towering progenitors of Japanese Sinology to gendered, diplomatic, and cultural dimensions of Sino-Japanese encounters; from Sinitic poetry to legal culture and revolutionary life; from art commerce and levels of literary expression to the quandaries of translation. In addition to offering a broad range of case studies, the volume is testimony to the methodological importance of a dynamic intra- and transregional approach for an understanding of the layered history of East Asia
Keywords: 20. Jahrhundert (ca. 1900 bis ca. 1999); 20th century; China; Japan; Festschrift; Aufsatzsammlung; Bibliografie; Fogel, Joshua A.; Geschichte; Geschichtsschreibung; Gesellschaft; Politik; Kultur